2017
DOI: 10.5935/abc.20170177
|View full text |Cite
|
Sign up to set email alerts
|

Association of Multiple Genetic Variants with the Extension and Severity of Coronary Artery Disease

Abstract: BackgroundMetabolic syndrome (MS) is a condition that, when associated with ischemic heart disease and cardiovascular events, can be influenced by genetic variants and determine more severe coronary atherosclerosis.ObjectivesTo examine the contribution of genetic polymorphisms to the extension and severity of coronary disease in subjects with MS and recent acute coronary syndrome (ACS).MethodsPatients (n = 116, 68% males) aged 56 (9) years, with criteria for MS, were prospectively enrolled to the study during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The manifestation and severity of CAD and hypertension depend on inherited predisposition combined with environmental factors. 28,29 Identification of factors for genetic risk of hypertension is thus essential for risk prediction of CAD and/or hypertension. Moreover, it has been suggested that the enhanced progression of these diseases is the result of renalase activity alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The manifestation and severity of CAD and hypertension depend on inherited predisposition combined with environmental factors. 28,29 Identification of factors for genetic risk of hypertension is thus essential for risk prediction of CAD and/or hypertension. Moreover, it has been suggested that the enhanced progression of these diseases is the result of renalase activity alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestation and severity of CAD and hypertension depend on inherited predisposition combined with environmental factors . Identification of factors for genetic risk of hypertension is thus essential for risk prediction of CAD and/or hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies have identified numerous loci for the CAD and one of the main susceptibility loci is placed at chromosome 15q26.1 which exists the single nucleotide polymorphism in the form of rs17514846 ( Yang et al, 2020 ). Several case-control and meta -analysis studies have shown the relation between LPL gene and CAD ( Xu et al, 2019 , Javorsky et al, 2007 , Daoud et al, 2013 , Fischer et al, 2018 , Ma et al, 2018 , Shahid et al, 2017 , Xie, 2017 ). The accurate genetic and molecular or any other mechanism which affects the LPL and human disease is poorly understood and LDL was interrelated towards certain heterogenous disorders which involve limited cardiovascular disorders ( Hartley et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%